Smart building façades using nanoparticle thermochromic technology: from fabrication to implementation - Aburas, Marina (2020)
Glass windows are integral to almost any building design, letting in natural light and offering views to connect our living spaces with the outside. They also play a major role in the energy consumption of buildings, and can account for up to 50% of energy used by HVAC and lighting systems. Thermochromic window technologies offer energy-saving capabilities by regulating window optical properties in response to real-time outdoor temperature. Prior thermochromic technology research focused heavily on material development, with little consideration of end-user options and preferences. To this end, the main research topic addressed by this thesis is the comprehensive trade-off between optical properties and the applicability of nanoparticle thermochromic technologies for use in façade systems. The research opens by identifying limitations of existing studies into thermochromic smart windows and provides novel approaches to fill the gaps. The first part of the investigation presents the fabrication of in-house nanoparticle thermochromic glass with variable luminous transmittance (30 to 75%) and infrared modulating capability (2 to 6%), tuned by adjusting the thickness of spin-coated thin-films. Subsequently, the effects of thin-film thickness on transmittance, solar modulation, energy saving, and visual and thermal performance were explored via building simulations for Hot Desert, Mediterranean, Temperate Oceanic, and Subarctic climates. The thickest film (Tlum = 30%) showed the highest relative energy saving over a comparatively tinted window for a Hot Desert climate (in-line with the current consensus that thermochromic windows are best suited for warmer climates), whereas in Subarctic climates this occurred with thinner films (Tlum = 75%). The thermochromic windows were shown to reduce overall peak loads and visual discomfort in the space. Finally, the effect of varying transmittance of the thermochromic coatings on visual comfort was studied to conclude the research. The test films were chosen to closely match the visible properties of the developed glazing with varying CCT (~2300 to 6200K). Window films were tested under simulated daylight, where various methods were used to quantify human perception and performance. The study found participants were able to correctly differentiate between the warmer CCT spaces, noting lighting to be more natural under neutral as opposed to warmer CCT window films, and incorrectly associating decrease in CCT with a decrease in brightness levels. The significance of this work lies in the holistic investigation of thermochromic technologies, offering valuable insights for coating fabrication tailored to building user preferences. Overall, this should help improve the way smart windows are incorporated into façade designs.